The bipolar child : the definitive and reassuring guide to childhood's most misunderstood disorder - Papolos, Demitri F.; Papolos, Janice (New York : Broadway Books, 2006)
A revised edition of this study discusses the diagnosis and treatment of early onset bipolar disorder in children, arguing that many youngsters who are currently being treated for ADHD and depression may be suffering from the early stages of manic depression, offering new information on mood-stabilizing drugs, omega-3 fatty acids, and educational opportunities.
PART I: DIAGNOSIS AND TREATMENT: Voices from the front -- The diagnostic dilemma -- How to find good treatment -- Prescriptions for treatment -- The genetic aspects of bipolar disorder -- PART II: INSIDE THE BRAIN AND MIND: The psychological dimensions -- What causes this condition? -- PART III: LIVING AND COPING WITH BIPOLAR DISORDER: The impact on the family -- School: a child's world beyond home -- The neuropsychological testing of a bipolar child -- Navigating the shoals of adolescence -- When a child is hospitalized -- The insurance man -- PART IV: LIFE GOES ON: Agenda for the future -- The bipolar child questionnaire.
Includes bibliographical references (p. [444]-459) and index.
Keywords: Bipolar Disorder; Child, Preschool; Child; Bipolar disorder in children; Depression in children; Psychoses in children; Manic-depressive illness; Depression (Psychology); Mental illness; Children -- Mental health